Studies on the Influence of Formulation and Processing Factors on the Drug Release from Multiparticulate Systems - K. V. R. N. S., Ramesh (Asian Journal of Pharmaceutics (AJP), 2020)
Background: Multiparticulate delivery systems are being increasingly recognized as more beneficial over single unit products because of more uniform distribution in gastrointestinal tract, less chance of dose dumping, better control on drug release, and more bioavailability with negligible variation among different individuals. Pellets are one commonly employed multi-particulate dosage form. New polymers need to be explored for their utility in palletization process. Objective: The goal of the investigation is to assess the feasibility of employing inclusion complex of poorly soluble drug furosemide in the design of slow-release pellets and investigate the usefulness of almond gum as a pelletizing agent. Materials and Methods: Inclusion complex of furosemide in sulfobutyl ether7-beta-cyclodextrin is prepared to enhance its dissolution. Pellets of inclusion complex are prepared by extrusion and spheronization employing almond gum as the spheronizing agent. The influence of almond gum proportion and speed of spheronization on the characteristics of pellets and drug release is investigated. Results: Inclusion complexation converted crystalline furosemide into an amorphous form, enhancing its dissolution. With changes in the percentage of almond gum and speed of spheronization, the size of the pellets could be varied which ranged from 640 to 1305 Î¼. Conclusion: Employing the inclusion complex of poorly soluble drugs for preparing SR pellets is a novel approach which ensures prompt, but slow-release spread over 12 h in the gastric fluids.